Securing the Risk. - Hoffmann, Leah (Communications of the ACM, 2013)
An interview with computer scientist and computer programmer Peter G. Neumann is presented. Background is presented on Neumann's career and achievements in computer science. He discusses his reasons for starting a career in computer science after having studied applied mathematics at Harvard University. He describes how he became involved with the Multics computer operating system (OS) project at Bell Laboratories. His reasons for leaving Bell Laboratories and joining nonprofit research center SRI International are also discussed.